Relapses of juvenile idiopathic arthritis in adulthood: A monocentric experience. - Laura Scagnellato; Giacomo Cozzi; Ilaria Prosepe; Mariagrazia Lorenzin; Andrea Doria; Giorgia Martini; Francesco Zulian; Roberta Ramonda (PLoS ONE, 2024)
Introduction Our aim was to describe a monocentric cohort of young adult patients with juvenile idiopathic arthritis (JIA), assessing the risk of relapse after transition to adult care. Methods We conducted a retrospective study and collected clinical, serological, and demographic data of young adult patients (18-30 years old) referred to the Transition Clinic of a single Italian centre between January 2020 and March 2023. Patients with systemic-onset JIA were excluded. Primary outcome was disease relapse, defined by Wallace criteria. Risk factors were analysed by Cox proportional hazards regression. Results Fifty patients with age 18-30 years old were enrolled in the study and followed for a median 30 months. The median disease duration at transition was 15 years. Twenty (40%) patients were on conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) and 38 (76%) were on biological DMARDs through adulthood. Twenty-three patients relapsed after transitioning to adult care for a median 9-month follow-up (IQR 0-46.5). Most relapses involved the knees (69.6%). The univariate analysis identified monoarthritis (HR 4.67, CI 1.069-20.41, p value = 0.041) as the main risk factor for relapse within the first 36 months of follow-up. Early onset, ANA positivity, past and ongoing treatment with csDMARDs or bDMARDs, therapeutic withdrawal, and disease activity within 12 months before transition did not significantly influence the risk of relapse. Conclusion In JIA patients, the risk of relapse after transitioning to adult care remains high, irrespective of disease subtype and treatment. The main risk factor for the early occurrence of articular activity is monoarticular involvement.